Pengaruh Stress Kerja, Lingkungan Kerja, dan Sistem Kompensasi Terhadap Prestasi Kerja Pada karyawan PT. Starfood Internasional Kandangsemangkon Lamongan - Suyitno Suyitno; Yulie Wahyuningsih (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
This study aims to determine the level of influence of work stress, work environment, and compensation system on work performance at PT. Starfood International Kandangsemangkon Lamongan. This research is an explanative research using a quantitative approach. The subjects of this study were employees of PT. Starfood International Kandangsemangkon Paciran Lamongan. With a sample of 33 respondents, data collection using questionnaires, interviews, and observations, the sampling technique is cluster sampling , because the study was conducted during the COVID-19 pandemic the sample used was limited to employees who were activated during the pandemic, while data analysis was carried out using multiple linear regression analysis. The results of the study at a significance level of 0.05 indicate that: 1) Job stress has a positive effect on employee work performance, as indicated by the t-test results of 1.969 with a significance of 0.059; 2) The employee's work environment has a positive and significant effect on employee work performance, which is shown from the results of the t-test of 5.972 with a significance of 0.000; 3) The compensation system has a positive and significant effect on employee performance, which is shown from the results of the t-test of 3.812 with a significance of 0.001; 4) Work stress, work environment, and employee compensation system together have an effect on employee work performance, which is shown from the results of the calculated F test of 62.210 with a significance of 0.000. The value of the coefficient of determination in this study is 0.825. It means that the ability to work stress, work environment, and compensation system is 82.5% while the remaining 17.5% is explained by other variables outside the model..